Rasionalitas Orang Tua Menyekolahkan Anak Disabilitas di SMPIT Al-Ikhlas Mantren - Wardana, Yusril Indra (Paradigma, 2022)
Education is the right of every citizen in Indonesia, including for children with disabilities. Many parents of children with disabilities have difficulty finding schools to provide the best education for their children. It is a dilemma for parents to send their children with disabilities to public schools, special schools, or inclusive schools. The purpose of this study is to find out how the rationality of parents finally sends children with disabilities to SMPIT Al-Ikhlas Mantren. This research is a qualitative research with a verstehen approach. The location of this research is at SMPIT Al-Ikhlas Mantren. The research subjects consisted of parents/guardians of children with disabilities, school principals, and inclusive classroom teachers. Data collection techniques used two techniques, namely primary and secondary in the form of interviews and documentation. Data were analyzed by data reduction, data presentation, and drawing conclusions. The data were studied using Max Weber’s theory of rational action. The results of this study are that there are various reasons that underlie the actions of parents of children with disabilities in determining education for their children, namely: parents’ education level, parents’ economic conditions, parents’ psychology, children’s personal desires, observations, recommendations from others, rejected /expelled from other schools, and mileage. These reasons can be grouped into internal factors and external factors. In addition, each parent/guardian has their own rationality in their decision to send inclusive children to this school. Each action taken by the subject can be categorized into four types of social action. These types of actions are instrumental rationality, value rationality, traditional action, and affective action. Keywords : Rationality, Parents, School